The Role of Digital Payment Technology in Improving Retail Operational Efficiency: A Review - Go, Ratna Yulika; Aini, Nur; Mutiarani, Tina; Yolanda, Ranti Okta; Sarbinny, Neni (Institut Teknologi Adhi Tama Surabaya, 2025)
Digital payment technology, including e-wallets, QR codes, and mobile banking, has become a crucial element in transforming the retail sector, particularly in simplifying transactions, reducing operational costs, and accelerating service processes. This study aims to analyze the role of digital payment technology in enhancing the operational efficiency of retail businesses. The research method used is a Systematic Literature Review (SLR) by exploring previous studies related to the perspectives of retail business owners who have adopted digital payments, as well as the challenges faced in its implementation. The research results indicate that out of 380 datasets collected, a screening and selection process was conducted based on specific criteria, yielding 15 relevant papers. The findings reveal that digital payment technology plays a significant role in improving efficiency by reducing transaction times, enhancing data management, and optimizing human resources. However, challenges such as infrastructure limitations, data security issues, and digital literacy among business owners remain obstacles that need to be addressed.